Change in VA Community Living Centers 2004–2011: Shifting Long-Term Care to the Community. Issue 2 (15th March 2018) - Thomas, Kali S.; Cote, Danielle; Makineni, Rajesh; Intrator, Orna; Kinosian, Bruce; Phibbs, Ciaran S.; Allen, Susan M.
ABSTRACT: The United States Department of Veterans Affairs (VA) is facing pressures to rebalance its long-term care system. Using VA administrative data from 2004–2011, we describe changes in the VA's nursing homes (called Community Living Centers [CLCs]) following enactment of directives intended to shift CLCs' focus from providing long-term custodial care to short-term rehabilitative and post-acute care, with safe and timely discharge to the community. However, a concurrent VA hospice and palliative care expansion resulted in an increase in hospice stays, the most notable change in type of stay during this time period. Nevertheless, outcomes for Veterans with non-hospice short and long stays, such as successful discharge to the community, improved. We discuss the implications of our results for simultaneous implementation of two initiatives in VA CLCs.